THE HAPPINESS CONTEXT IN THE INDONESIAN CULTURE (The Role of Sociolinguistics in Translating a Culture) - Nadir, Muh (Journal of Islam and Science, 2016)
This essay will discuss the interpretation of sociolinguistics in translating the culture of Indonesia regarding the happiness context. As an emotional concept, happiness or kebahagiaan in the Indonesian language has an ambiguity in articulation when someone percept it as a conditional of a joyfull the one feels. Since the word has an ambiguity in meaning, the role of Sociolinguistics is significant in identifying what Indonesian people coin when say aku bahagia (I’m happy). The main argument of this paper focuses on the term kebahagiaan in the different situations and people. The first part of this essay will discuss the term of the happiness in the global meaning and its correlation with the term of emotion. The second part addresses the term kebahagiaan in the Indonesian language and its derivation of meaning.  The last part of the essay speaks about how to measure the concept of the word kebahagiaan the Indonesian people use in their daily life.